Preparation method and application of anisotropic dual-network packaged photo-thermal composite phase change material

By preparing an anisotropic double-network structure of cellulose nanofiber/graphene nanosheet/polypyrrole-modified flower-like ZnCo-ZIF composite aerogel, the problem of insufficient light-to-heat conversion performance of organic phase change materials was solved, and efficient light-to-heat conversion and light-to-heat-electric performance were achieved, which is suitable for light-to-heat-electric generators.

CN120795878APending Publication Date: 2025-10-17GUIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510996125.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing organic phase change materials (PCMs) have deficiencies in light-to-heat conversion performance and thermal energy storage/release rate, which limits their application in efficient solar energy capture and real-time storage, and traditional strategies lead to a decrease in latent heat enthalpy.

Method used

A photothermal composite phase change material was prepared by chemical deposition, freeze drying and vacuum-assisted melt encapsulation using cellulose nanofiber (CNF)/graphene nanosheet (GNP)/polypyrrole-modified flower-like ZnCo-ZIF composite aerogel (CGxFy) with an anisotropic double network structure, to form an anisotropic double network encapsulated PW@CGxFy composite phase change material.

Benefits of technology

It achieves high light-to-heat conversion efficiency (93.4%) and excellent light-to-thermal-electrical performance at a low thermal conductive filler content, outputting an open-circuit voltage (203.0mV) and short-circuit current (33.8mA), making it suitable for light-to-thermal-electrical generators and solving the problem of insufficient light-to-thermal conversion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795878A_ABST
    Figure CN120795878A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photo-thermal composite phase change heat storage materials, and particularly discloses a preparation method and application of an anisotropic dual-network packaged photo-thermal composite phase change material, and the composite phase change material is PW (at) CGxFy. The invention provides a method for preparing a PW (at) CGxFy composite phase change material through simple chemical deposition, freeze drying and vacuum-assisted fusion packaging strategies. The flower-like ZnCo-ZIF-coated PPy (F) photo-thermal filler is prepared through a hydrothermal method and a subsequent chemical deposition technology. And then, carrying out directional freeze drying on the prepared CNF / GNP / F uniform dispersion liquid to prepare the CGxFy composite aerogel. And finally, immersing PW into the aerogel by adopting a vacuum-assisted fusion packaging method, so as to obtain the final PW (at) CGxFy composite phase change material. The PW (at) CGxFy composite phase change material provided by the invention shows efficient light-heat conversion performance (93.4%), and can be used as a light-heat conversion material in a light-heat-electricity generator. The technology is controllable, and large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of light-heat composite phase change heat storage materials, in particular to a preparation method and application of an anisotropic double-network encapsulated light-heat composite phase change material. BACKGROUND

[0002] The massive consumption of fossil fuels has caused a series of social problems such as energy crisis, environmental pollution, global warming, etc. Therefore, it is urgent to make full use of clean and sustainable energy to alleviate these problems. Among clean energy, solar energy is more favored by researchers due to its advantages such as renewability, versatility and affordability. However, its inherent intermittency and instability can easily lead to unstable energy output and supply-demand mismatch problems. Solid-liquid organic phase change materials (PCMs) with high energy storage density, small volume change, easy processing, low cost, almost constant phase change temperature, etc. are considered as an ideal thermal energy storage material. Unfortunately, most organic PCMs have inherent shortcomings such as easy leakage during phase change process, low thermal conductivity (TC), poor light-heat conversion ability, etc., which limits their application in efficient solar energy capture and real-time storage.

[0003] To solve the above problems, domestic and foreign researchers have gradually explored lightweight porous three-dimensional (3D) anisotropic networks with high efficient heat conduction and light-heat conversion performance for encapsulating organic PCMs to realize shape-stable composite PCMs (ss-CPCMs), so as to improve the light-heat conversion efficiency (ε). In recent years, 3D flower-like light-heat materials that can reflect and absorb sunlight multiple times have been gradually applied to the preparation of light-heat ss-CPCMs. However, flower-like light-heat materials have little effect on improving TC, which directly affects the heat storage / release rate of ss-CPCMs. In this regard, some studies have combined a large number of high-TC nano fillers with flower-like light-heat materials, but this strategy leads to a significant decrease in latent heat enthalpy, which is not conducive to light-heat storage. Therefore, it is still urgent to improve the ε of skeleton-supported ss-CPCMs.

[0004] Therefore, it is urgent to propose a preparation method of light-heat composite phase change material that can make up for the insufficient light-heat conversion performance of ss-CPCMs, which can then be used as a light-heat conversion material in a light-heat-electric generator. SUMMARY

[0005] To solve the problems in the prior art, the application provides a preparation method and application of an anisotropic double-network encapsulated photo-thermal composite phase change material, the cellulose nanofiber (CNF) / graphene nanosheet (GNP) / polypyrrole modified flower-like ZnCo-ZIF (F) composite aerogel (CGxFy) with an anisotropic double-network structure is prepared through simple chemical deposition and freeze-drying technology, and then the PW is further vacuum-assisted melt encapsulated to obtain the final PW@CGxFy composite phase change material. 2 The composite phase change material provided by the application exhibits outstanding photo-thermal conversion efficiency (93.4%) under simulated sunlight radiation, and the photo-thermal-electric device combined with the composite phase change material outputs objective open-circuit voltage (203.0 mV) and short-circuit current (33.8 mA), and can be used as a photo-thermal conversion material in a photo-thermal-electric generator; the application technology is controllable and can be produced on a large scale, and solves the problems mentioned in the background art.

[0006] To achieve the above object, the application provides the following technical scheme: a preparation method of an anisotropic double-network encapsulated photo-thermal composite phase change material, comprising the following steps:

[0007] S1, preparing flower-like ZnCo-ZIF through a hydrothermal method, then, performing chemical deposition of polypyrrole PPy to obtain flower-like ZnCo-ZIF@Ppy (referred to as F), that is, F photo-thermal filler;

[0008] S2, preparing a cellulose nanofiber CNF / graphene nanosheet GNPx uniform dispersion liquid, and adding the F photo-thermal filler obtained in step S1 into the uniform dispersion liquid, uniformly dispersing, and then freeze-drying to obtain CNF / GNPx / Fy (referred to as CGxFy), that is, CGxFy composite aerogel;

[0009] S3, immersing the CGxFy composite aerogel prepared in step S2 in a paraffin (PW) melt, and performing vacuum treatment, then, taking out and naturally cooling to room temperature to obtain the final PW@CGxFy composite phase change material. Wherein, x represents the concentration of GNP, and the range is 5-25 mg / mL; y represents the filling concentration of F, and the range is 5-35 mg / mL.

[0010] Preferably, in step S1, the preparation specifically comprises the following:

[0011] S11, adding Co(NO3)2·6H2O and Zn(NO3)2·6H2O into CH3OH, performing magnetic stirring to obtain a uniform solution A; at the same time, adding 2-MI into CH3OH, performing magnetic stirring to obtain a uniform solution B;

[0012] S12, under stirring, solution B is slowly dropped into solution A, and ultrasonic treatment is performed; then, the obtained uniform mixed solution is transferred into a high-pressure reaction kettle, and hydrothermal reaction is performed, and centrifugal washing is performed using CH3OH, C2H6O and DIW in sequence, the precipitate is dispersed in DIW to obtain a ZnCo-ZIF uniform water dispersion;

[0013] S13, C4H5N is dropped into the ZnCo-ZIF uniform water dispersion obtained in step S12, and strong stirring is performed to uniformly mix it, then, DBSA is slowly dropped, and stirring is performed in an ice-water bath, and FeCl3·6H2O is added, low-temperature preservation is performed, C4H5N is polymerized on the surface of the flower-shaped ZnCo-ZIF, then, centrifugal washing is performed on the reaction product using C2H6O and DIW in sequence to obtain ZnCo-ZIF@PPy, that is, F light-thermal filler.

[0014] Preferably, in step S11, the mass-volume ratio of Co(NO3)2·6H2O, Zn(NO3)2·6H2O, 2-MI and CH3OH is 825 mg: 275 mg: 650 mg: 17.5 mL; the magnetic stirring speed and time are 200-700 rpm and 0.3-1 h respectively.

[0015] In step S12, the stirring speed is 200-700 rpm, the power and time of ultrasonic treatment are 240 W and 0.1-0.5 h respectively, the temperature and time of the hydrothermal reaction are 90-120℃ and 2-5 h respectively, and the rotation speed and time of centrifugal washing are 3000-6000 rpm and 2-8 min respectively.

[0016] Preferably, in step S13, the mass-volume ratio of DBSA, C4H5N, ZnCo-ZIF and FeCl3·6H2O is 2.353 g: 0.1 mL: 40 mL: 50 mL; the concentration of the ZnCo-ZIF water dispersion is 6-10 mg / mL; the speed and time of strong stirring are 1000-2000 rpm and 0.5-2 h respectively; the temperature of the ice-water bath is 2-10℃, the stirring speed and time in the ice-water bath are 500-1500 rpm and 0.5-2 h respectively; the concentration of the FeCl3·6H2O is 0.3-0.8 M, the temperature and time of low-temperature preservation are 0-4℃ and 2-6 h respectively, and the rotation speed and time of centrifugal washing are 3000-7000 rpm and 2-8 min respectively.

[0017] Preferably, in step S2, the specific preparation comprises the following:

[0018] S21, gradually add GNP powder into the CNF uniform water dispersion, and cyclically perform magnetic stirring and ultrasonic treatment to obtain a uniform CNF / GNPx uniform dispersion;

[0019] S22, gradually adding the prepared F photothermal filler into the CNF / GNPx uniform dispersion liquid prepared in step S21, and performing strong stirring to obtain a CGxFy uniform dispersion liquid;

[0020] S23, pouring the CGxFy uniform dispersion liquid obtained in step S22 into an aluminum cover, and moving into a low-temperature refrigerator for gelation, then using liquid nitrogen for directional freezing, and performing freeze-drying to obtain a CGxFy aerogel.

[0021] Preferably, in step S21, the concentration of the CNF uniform aqueous dispersion liquid is 3-12 mg / mL, the concentration of the GNP is 5-25 mg / mL, the speed and time of the magnetic stirring are 500-2000 rpm and 1-3 h respectively, the ultrasonic power and time are 240 W and 1-4 h respectively, and the number of cycles is 2-5 times.

[0022] Preferably, in step S22, the concentration of the F photothermal filler is 5-35 mg / mL, and the speed and time of the strong stirring are 1000-3000 rpm and 4-8 h respectively.

[0023] In step S23, the temperature of the low-temperature refrigerator is 0-4°C, the gelation time is 8-16 h, and the temperature, pressure and time of the freeze-drying are -72°C, 2 Pa and 24-72 h respectively.

[0024] Preferably, in step S3, the preparation specifically includes the following: adding PW into an aluminum tank and moving into a vacuum oven to completely melt, then immersing the CGxFy composite aerogel prepared in step S2 into the PW melt, performing vacuum treatment to make the PW fully enter the CGxFy aerogel, taking it out, and using soft fabric to wipe off the excess PW melt on the surface to obtain the final PW@CGxFy composite phase change material.

[0025] Preferably, the mass ratio of the PW to the CGxFy composite aerogel is 20:1-5, the temperature of the vacuum oven is 60-90°C, and the pressure and time of the vacuum treatment are 80 Pa and 18-32 h respectively.

[0026] Preferably, the anisotropic double-network encapsulated PW@CGxFy photothermal composite phase change material is a paraffin (PW)@ / cellulose nanofiber (CNF) / graphene nanosheet (GNP) / polypyrrole modified flower-like ZnCo-ZIF (F) (referred to as PW@CGxFy).

[0027] In another aspect, to achieve the above object, the application further provides the following technical scheme: application of an anisotropic double-network encapsulated photo-thermal composite phase change material, which uses the photo-thermal composite phase change material as a light-heat conversion material in a light-heat-electricity generator.

[0028] The application has the following beneficial effects:

[0029] 1) The application provides a method for preparing a PW@CGxFy composite phase change material by simple chemical deposition, freeze-drying and vacuum-assisted melting encapsulation strategies. F photo-thermal fillers are prepared by a hydrothermal method and subsequent low-temperature chemical deposition technology. Then, a CGxFy composite aerogel is prepared by directional freeze-drying of a CNF / GNPx / Fy uniform dispersion liquid. Subsequently, the PW is vacuum-assisted melting encapsulated to obtain the final PW@CGxFy composite phase change material.

[0030] 2) The CGxFy composite aerogel provided by the application has an anisotropic double-network structure, which provides abundant adsorption sites for the PW and ensures excellent shape stability. In addition, the anisotropic network structure provides an effective phonon conduction network for the final PW@CGxFy composite phase change material. At the same time, the hierarchical porous structure of CGxFy increases the multiple reflection and absorption of sunlight, which endows the PW@CGxFy composite phase change material with outstanding light-heat conversion performance.

[0031] 3) The PW@CGxFy composite phase change material provided by the application exhibits excellent light-heat conversion efficiency (93.4%) at a low content of GNP heat-conducting fillers (2.8 wt%), and the light-heat-electricity system combined with it outputs a satisfactory open-circuit voltage (203.0 mV) and short-circuit current (33.8 mA). The PW@CGxFy composite phase change material can be used as a light-heat conversion material in a light-heat-electricity generator, which helps to alleviate the energy crisis caused by the large consumption of fossil fuels. Moreover, the application technology is controllable and can be produced on a large scale. BRIEF DESCRIPTION OF DRAWINGS

[0032] Figure 1 SEM images of ZnCo-ZIF and ZnCo-ZIF@PPy(F) prepared in the embodiments of the application and FTIR curves and XRD patterns of PPy, ZnCo-ZIF and F; (a) is ZnCo-ZIF, (b) is ZnCo-ZIF@PPy(F), (c) is the FTIR curves of PPy, ZnCo-ZIF and F, and (d) is the XRD patterns of PPy, ZnCo-ZIF and F;

[0033] Figure 2 SEM images of the longitudinal and transverse sections of the CG15F25 composite aerogel prepared in the embodiments of the application; (a1) and (a2) represent the longitudinal direction, and (b1) and (b2) represent the transverse direction;

[0034] Figure 3 SEM images of the embodiments of the present application PW@CNF, PW@CG15, PW@CF25, PW@CG5F25, PW@CG15F25 and PW@CG25F25; (a1) and (a2) represent PW@CNF, (b1) and (b2) represent PW@CG15; (c1) and (c2) represent PW@CF25; (d1) and (d2) represent PW@CG5F25; (e1) and (e2) represent PW@CG15F25; (f1) and (f2) represent PW@CG25F25;

[0035] Figure 4 Digital photos of the embodiments of the present application PW and PW@CGxFy in 80℃ heating stage, and FTIR spectra and XRD spectra of PW, PW@CNF, PW@CG15, PW@CF15 and PW@CG15F15; (a) is the digital photo of PW and PW@CGxFy in 80℃ heating stage; (a) is the FTIR spectra of PW, PW@CNF, PW@CG15, PW@CF15 and PW@CG15F15; (c) is the XRD spectra of PW, PW@CNF, PW@CG15, PW@CF15 and PW@CG15F15;

[0036] Figure 5 Phase transition enthalpy, phase transition temperature of the embodiments of the present application prepared PW, PW@CNF and PW@CGxF25, and phase transition enthalpy and phase transition temperature of PW@CG25F25 in 100 times of DSC cycle; (a) is the phase transition enthalpy (ΔH m and ΔH c ), (b) is the phase transition temperature (T m and T c ), (c) is the phase transition enthalpy of PW@CG25F25 in 100 times of DSC cycle, (d) is the phase transition temperature of PW@CG25F25 in 100 times of DSC cycle;

[0037] Figure 6 TC of the embodiments of the present application prepared PW, PW@CG15, PW@CG15Fy, and TC of PW@CF25 and PW@CGxF25; (a) is the TC of PW, PW@CG15, PW@CG15Fy, (b) is the TC of PW@CF25 and PW@CGxF25;

[0038] Figure 7UV-visible-near-infrared spectra of PPy, ZnCo-ZIF, ZnCo-ZIF@PPy and GNP prepared in the present invention, as well as UV-visible-near-infrared spectra of PW@CNF, PW@CG25, PW@CF25 and PW@CG25F25, and 100mW / cm 2 Time-temperature curves of the upper and lower surfaces of PW@CNF, PW@CG15, PW@CF25, and PW@CG15F25 samples under simulated sunlight, and 100 mW / cm 2 Time-temperature curves of the upper and lower surfaces of PW@CGxF25 under solar radiation; (a) UV-visible-near-infrared spectra of PPy, ZnCo-ZIF, ZnCo-ZIF@PPy, and GNP; (b) UV-visible-near-infrared spectra of PW@CNF, PW@CG25, PW@CF25, and PW@CG25F25; (c1) upper surfaces of PW@CNF, PW@CG15, PW@CF25, and PW@CG15F25 samples; (c2) lower surfaces of PW@CNF, PW@CG15, PW@CF25, and PW@CG15F25 samples; (d1) upper surface of PW@CGxF25; (d2) lower surface of PW@CGxF25.

[0039] Figure 8 The photothermal-electric (STE) generator constructed by synergistically constructing PW@CNF and PW@CGxF25 prepared in the embodiment of the present invention is 100mW / cm 2 Schematic diagram of the output open-circuit voltage and short-circuit current under simulated sunlight, and the output V of the STE system built with PW@CG25F25 under different light intensities OC and I SC Schematic diagram and five on-off light cycle experiments using the PW@CG25F25-based STE device V OC and I SC Schematic diagram; (a1) is the open circuit voltage V under simulated sunlight OC ; (a2) is the short-circuit current I under simulated sunlight SC (b1) is the output V of the STE system built with PW@CG25F25 under different light intensities OC (b2) is the output of the STE system built with PW@CG25F25 under different light intensities. SC (c1) is the STE device V based on PW@CG25F25 in the 5-time on-off light cycle experiment OC (c2) is the STE device I based on PW@CG25F25 in the 5-time on-off light cycle experiment SC . DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the scope of protection of the present application.

[0041] It should be noted that the embodiments and features in the embodiments can be combined with each other without conflict. It should be noted that similar reference numerals and letters represent similar items in the following drawings, and thus, once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings.

[0042] In the description of the present application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship commonly used when the product of the present application is used, or the orientation or positional relationship commonly understood by a person skilled in the art, and are only for the convenience of describing the present application and simplifying the description, and thus cannot be understood as indicating or implying that the indicated device or element must have a particular orientation, be constructed and operated in a particular orientation, and thus cannot be understood as limiting the present application. In addition, the terms "first", "second", and the like are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0043] In the description of the present application, it should also be noted that, unless otherwise explicitly specified and limited, the terms "arrange", "mount", "connect", and "connect" should be understood broadly, for example, can be fixedly connected, or can be detachably connected, or integrally connected; can be mechanically connected, or can be electrically connected; can be directly connected, or can be indirectly connected through an intermediate medium, or can be the communication inside two elements. For a person of ordinary skill in the art, the specific meaning of the above terms in the present application can be understood according to the specific circumstances.

[0044] Embodiment 1

[0045] A PW@CG15 composite phase change material, the preparation method is as follows:

[0046] Step S1: preparing a CNF / GNP15 uniform dispersion liquid, and obtaining a CNF / GNP15 (abbreviated as CG15) composite aerogel by freeze-drying;

[0047] Specifically, step S11: 0.6 g of GNP powder was gradually added into the CNF uniform aqueous dispersion (10 mg / mL), and the magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were cycled for 3 times to obtain a uniform CG15 dispersion;

[0048] Step S12: The CG15 dispersion obtained in step S11 was poured into an aluminum cap and moved into a low-temperature refrigerator for gelation, then directional freezing was performed using liquid nitrogen, and freeze-drying was performed (-72℃, 2Pa, 48h) to obtain a CG15 aerogel.

[0049] Step S2: The CG15 composite aerogel prepared in step S1 was immersed in a PW melt and vacuum treated, then it was taken out and naturally cooled to room temperature to obtain a final PW@CG15 composite phase change material.

[0050] Specifically, step S21: 20 g of PW was added to an aluminum pot and moved into an 80℃ vacuum oven for complete melting, then the CG15 aerogel prepared in step S1 was immersed in the PW melt and vacuum treated (80Pa, 24h) to allow the PW to fully enter the CG15 aerogel, it was taken out and the excess PW melt on the surface was wiped off using a soft fabric to obtain a final PW@CG15 composite phase change material.

[0051] Example 2

[0052] A PW@CG15F5 composite phase change material was prepared as follows:

[0053] Step S1: flower-like ZnCo-ZIF was prepared by a hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy was performed to obtain flower-like ZnCo-ZIF@PPy (referred to as F) photo-thermal filler;

[0054] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH, and magnetic stirring was performed at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH, and magnetic stirring was performed at 500 rpm for 0.5 h to obtain a uniform solution B;

[0055] Step S12: Solution B of step S11 was slowly dripped into solution A under stirring condition of 500 rpm, and ultrasonic treatment was carried out at a power of 240 W for 0.25 h, then the obtained uniform mixed solution was transferred into a high-pressure reaction kettle at 105 ℃, and hydrothermal reaction was carried out for 3 h, and centrifugal washing was carried out in sequence using CH 3 OH, C 2 H 6 O and DIW (5000 rpm, 5 min), the precipitate was dispersed in DIW to obtain a ZnCo-ZIF uniform water dispersion;

[0056] Step S13: 0.1 mL of C 4 H 5 N was dripped into 50 mL of the ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and uniform mixing was carried out under strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly dripped, and stirring was carried out in an ice-water bath at 2-10 ℃ (1000 rpm, 0.5 h), and 50 mL of FeCl 3 ·6H 2 O (0.6 M) was added, and the temperature was kept at 2-10 ℃ for 6 h, so that C 4 H 5 N was polymerized on the surface of the flower-shaped ZnCo-ZIF, then centrifugal washing was carried out in sequence using C 2 H 6 O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) photo-thermal filler.

[0057] Step S2: A CNF / GNP15 uniform dispersion was prepared, and the F photo-thermal filler obtained in step S1 was added and uniformly dispersed, and then freeze-drying was carried out to obtain a CNF / GNP15 / F5 (referred to as CG15F5) composite aerogel;

[0058] Specifically, step S21: 0.6 g of GNP powder was gradually added into a CNF uniform water dispersion (10 mg / mL), and magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were carried out in cycles for 3 times to obtain a uniform CNF / GNP15 uniform dispersion;

[0059] Step S22: 0.2 g of the F photo-thermal filler prepared in step S1 was gradually added into the CNF / GNP15 uniform dispersion prepared in step S21, and strong stirring was carried out at 2000 rpm for 6 h to obtain a CNF / GNP15 / F5 (referred to as CG15F5) uniform mixed dispersion;

[0060] Step S23: The CG15F5 uniform dispersion obtained in step S22 was poured into an aluminum cover, and was moved into a low-temperature refrigerator for gelation, then directional freezing was carried out using liquid nitrogen, and freeze-drying was carried out (-72 ℃, 2 Pa, 48 h) to obtain a CG15F5 aerogel.

[0061] Step S3: The CG15F5 composite aerogel prepared in step S2 is immersed in the PW melt and vacuum treated, then taken out and naturally cooled to room temperature to obtain the final PW@CG15F5 composite phase change material.

[0062] Specifically, step S31: 20 g of PW is added to an aluminum tank and moved into an 80°C vacuum oven to completely melt, then the CG15F5 aerogel prepared in step S2 is immersed in the PW melt and vacuum treated (80 Pa, 24 h) to make the PW fully enter the CG15F5 aerogel, and then taken out and wiped with a soft fabric to remove the excess PW melt on the surface to obtain the final PW@CG15F5 composite phase change material.

[0063] Example 3

[0064] A PW@CG15F15 composite phase change material is prepared by the following method:

[0065] Step S1: flower-like ZnCo-ZIF is prepared by a hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy is performed to obtain flower-like ZnCo-ZIF@PPy (referred to as F) photo-thermal filler;

[0066] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O are added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI is added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution B;

[0067] Step S12: under the condition of 500 rpm stirring, solution B of step S11 is slowly dropped into solution A, and ultrasonic treatment is performed at a power of 240 W for 0.25 h, then the obtained uniform mixed solution is transferred to a 105°C high-pressure reaction kettle for hydrothermal reaction for 3 h, and centrifugal washing is performed in sequence with CH3OH, C2H6O and DIW (5000 rpm, 5 min), the precipitate is dispersed in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0068] Step S13: 0.1 mL of C4H5N was added into 50 mL of ZnCo-ZIF aqueous dispersion (10 mg / mL) obtained in step S12, and was uniformly mixed by strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly added, transferred into an ice water bath at 2-10°C and stirred (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10°C for 6 h, so that C4H5N was polymerized on the surface of the flower-like ZnCo-ZIF, then the reaction product was washed by centrifugation (5000 rpm, 5 min) using C2H6O and DIW in sequence, and ZnCo-ZIF@PPy (referred to as F) photo-thermal filler was obtained.

[0069] Step S2: A CNF / GNP15 uniform dispersion was prepared, and the F photo-thermal filler obtained in step S1 was added, and after uniform dispersion, CNF / GNP15 / F15 (referred to as CG15F15) composite aerogel was obtained by freeze-drying.

[0070] Specifically, step S21: 0.6 g of GNP powder was gradually added into the CNF uniform aqueous dispersion (10 mg / mL), and the magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were cycled for 3 times to obtain a uniform CNF / GNP15 uniform dispersion;

[0071] Step S22: 0.6 g of F photo-thermal filler prepared in step S1 was gradually added into the CNF / GNP15 uniform dispersion prepared in step S21, and was strongly stirred at 2000 rpm for 6 h to obtain a CNF / GNP15 / F15 (referred to as CG15F15) uniform mixed dispersion;

[0072] Step S23: The CG15F15 uniform dispersion obtained in step S22 was poured into an aluminum cap and moved into a low-temperature refrigerator for gelation, then was directionally frozen using liquid nitrogen, and was freeze-dried (-72°C, 2 Pa, 48 h) to obtain a CG15F15 aerogel.

[0073] Step S3: The CG15F15 composite aerogel prepared in step S2 was immersed in a PW melt and vacuum treated, then was taken out and naturally cooled to room temperature to obtain a final PW@CG15F15 composite phase change material.

[0074] Specifically, step S31: 20 g of PW was added into an aluminum tank and moved into a vacuum oven at 80°C to completely melt, then the CG15F15 aerogel prepared in step S2 was immersed in the PW melt, vacuum treatment (80 Pa, 24 h) was carried out to make the PW fully enter the CG15F15 aerogel, and the PW@CG15F15 composite phase change material was obtained by removing the excess PW melt on the surface of the aerogel using a soft fabric.

[0075] Example 4

[0076] A PW@CG15F25 composite phase change material was prepared by the following method:

[0077] Step S1: flower-like ZnCo-ZIF was prepared by a hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy was carried out to obtain flower-like ZnCo-ZIF@PPy (referred to as F) light-heat filler;

[0078] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution B;

[0079] Step S12: under the condition of 500 rpm stirring, solution B of step S11 was slowly dropped into solution A, and ultrasonic treatment was carried out at a power of 240 W for 0.25 h, then the obtained uniform mixed solution was transferred to a high-pressure reaction kettle at 105°C, and hydrothermal reaction was carried out for 3 h, and centrifugal washing was carried out in sequence using CH3OH, C2H6O and DIW (5000 rpm, 5 min), the precipitate was dispersed in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0080] Step S13: 0.1 mL of C4H5N was dropped into 50 mL of ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and strong stirring was carried out at 1500 rpm for 0.5 h to make it uniformly mixed, then 2.353 g of DBSA was slowly dropped, and transferred to an ice water bath at 2-10°C for stirring (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10°C for 6 h, so that C4H5N was polymerized on the surface of the flower-like ZnCo-ZIF, then the reaction product was centrifugally washed in sequence using C2H6O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) light-heat filler.

[0081] Step S2: preparing a CNF / GNP15 uniform dispersion liquid, and adding the F photothermal filler obtained in step S1 into the CNF / GNP15 uniform dispersion liquid, uniformly dispersing the F photothermal filler, and then freeze-drying to obtain a CNF / GNP15 / F25 (abbreviated as CG15F25) composite aerogel;

[0082] Specifically, step S21: gradually adding 0.6 g of GNP powder into a CNF uniform water dispersion liquid (10 mg / mL), and performing magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) for 3 times, to obtain a uniform CNF / GNP15 uniform dispersion liquid;

[0083] Step S22: gradually adding 1.0 g of the F photothermal filler prepared in step S1 into the CNF / GNP15 uniform dispersion liquid prepared in step S21, and performing strong stirring at 2000 rpm for 6 h, to obtain a CNF / GNP15 / F25 (abbreviated as CG15F25) uniform mixed dispersion liquid;

[0084] Step S23: pouring the CG15F25 uniform dispersion liquid obtained in step S22 into an aluminum cover, and moving into a low-temperature refrigerator for gelation, then using liquid nitrogen for directional freezing, and performing freeze-drying (-72℃, 2 Pa, 48 h) to obtain a CG15F25 aerogel.

[0085] Step S3: immersing the CG15F25 composite aerogel prepared in step S2 into a PW melt, and performing vacuum treatment, then taking it out and naturally cooling to room temperature to obtain a final PW@CG15F25 composite phase change material.

[0086] Specifically, step S31: adding 20 g of PW into an aluminum pot, and moving into a 80℃ vacuum oven to completely melt, then immersing the CG15F25 aerogel prepared in step S2 into the PW melt, and performing vacuum treatment (80 Pa, 24 h) to make the PW fully enter the CG15F25 aerogel, taking it out, and using a soft fabric to wipe off the excess PW melt on the surface, to obtain a final PW@CG15F25 composite phase change material.

[0087] Example 5

[0088] A PW@CG15F35 composite phase change material, and a preparation method is as follows:

[0089] Step S1: preparing a flower-like ZnCo-ZIF by a hydrothermal method, then performing low-temperature chemical deposition (poly-pyrrole) PPy, to obtain a flower-like ZnCo-ZIF@PPy (abbreviated as F) photothermal filler;

[0090] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH, and magnetic stirring was performed at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH, and magnetic stirring was performed at 500 rpm for 0.5 h to obtain a uniform solution B;

[0091] Step S12: Under the condition of 500 rpm stirring, solution B of step S11 was slowly dropped into solution A, and ultrasonic treatment was performed at 240 W power for 0.25 h, then the obtained uniform mixed solution was transferred to a 105℃ high-pressure reaction kettle, and hydrothermal reaction was performed for 3 h, and centrifugal washing was performed in turn using CH3OH, C2H6O and DIW (5000 rpm, 5 min), and the precipitate was dispersed in DIW to obtain a ZnCo-ZIF uniform water dispersion;

[0092] Step S13: 0.1 mL of C4H5N was dropped into 50 mL of ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and uniform mixing was performed by strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly dropped, and transferred to an ice water bath at 2-10℃ for stirring (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10℃ for 6 h, so that C4H5N was polymerized on the surface of the flower-like ZnCo-ZIF, then the reaction product was centrifugally washed in turn using C2H6O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) photo-thermal filler.

[0093] Step S2: A CNF / GNP15 uniform dispersion was prepared, and the F photo-thermal filler obtained in step S1 was added to uniformly disperse it, and then freeze-drying was performed to obtain a CNF / GNP15 / F35 (referred to as CG15F35) composite aerogel;

[0094] Specifically, step S21: 0.6 g of GNP powder was gradually added to a CNF uniform water dispersion (10 mg / mL), and magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were cyclically performed for 3 times to obtain a uniform CNF / GNP15 uniform dispersion;

[0095] Step S22: 1.4 g of the F photo-thermal filler prepared in step S1 was gradually added to the CNF / GNP15 uniform dispersion prepared in step S21, and strong stirring was performed at 2000 rpm for 6 h to obtain a CNF / GNP15 / F35 (referred to as CG15F35) uniform mixed dispersion;

[0096] Step S23: Pour the CG15F35 uniform dispersion solution obtained in step S22 into an aluminum cap and move into a low-temperature refrigerator for gelation, then use liquid nitrogen for directional freezing and perform freeze-drying (-72°C, 2Pa, 48h) to obtain the CG15F35 aerogel.

[0097] Step S3: Immerse the CG15F35 composite aerogel prepared in step S2 into the PW melt and perform vacuum treatment, then take it out and naturally cool to room temperature to obtain the final PW@CG15F35 composite phase change material.

[0098] Specifically, step S31: Put 20g of PW into an aluminum pot and move it into an 80°C vacuum oven to completely melt, then immerse the CG15F35 aerogel prepared in step S2 into the PW melt and perform vacuum treatment (80Pa, 24h) to make the PW fully enter the CG15F35 aerogel, take it out and use soft fabric to wipe off the excess PW melt on the surface to obtain the final PW@CG15F35 composite phase change material.

[0099] Example 6

[0100] A PW@CF25 composite phase change material is prepared by the following method:

[0101] Step S1: Prepare flower-like ZnCo-ZIF by hydrothermal method, then perform low-temperature chemical deposition (poly-pyrrole) PPy to obtain flower-like ZnCo-ZIF@PPy (abbreviated as F) photo-thermal filler;

[0102] Specifically, step S11: Put 825mg of Co(NO3)2·6H2O and 275mg of Zn(NO3)2·6H2O into 17.5mL of CH3OH and perform magnetic stirring at 500rpm for 0.5h to obtain a uniform solution A; at the same time, put 650mg of 2-MI into 17.5mL of CH3OH and perform magnetic stirring at 500rpm for 0.5h to obtain a uniform solution B;

[0103] Step S12: Under the condition of 500rpm stirring, slowly drop solution B of step S11 into solution A, perform ultrasonic treatment at a power of 240W for 0.25h, then transfer the obtained uniform mixed solution to a 105°C high-pressure reaction kettle and perform hydrothermal reaction for 3h, and sequentially use CH3OH, C2H6O and DIW for centrifugal washing (5000rpm, 5min), disperse the precipitate in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0104] Step S13: 0.1 mL of C4H5N was added into 50 mL of ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and stirred at 1500 rpm for 0.5 h to make them uniformly mixed, then 2.353 g of DBSA was slowly added, transferred to an ice water bath at 2-10°C and stirred (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and kept at 2-10°C for 6 h to make C4H5N polymerize on the surface of the flower-like ZnCo-ZIF, then the reaction product was washed by centrifugation (5000 rpm, 5 min) using C2H6O and DIW in sequence, and ZnCo-ZIF@PPy (referred to as F) photo-thermal filler was obtained.

[0105] Step S2: The F photo-thermal filler obtained in step S1 was added into the CNF dispersion liquid, and uniformly dispersed to obtain CNF / F25 (referred to as CF25) composite aerogel by freeze-drying.

[0106] Specifically, step S21: 1.0 g of F photo-thermal filler prepared in step S1 was gradually added into the CNF uniform dispersion liquid (10 mg / mL), and stirred at 2000 rpm for 6 h to obtain a CNF / F25 (referred to as CF25) uniform mixed dispersion liquid.

[0107] Step S22: The CF25 uniform dispersion liquid obtained in step S21 was poured into an aluminum cover and moved into a low-temperature refrigerator for gelation, then liquid nitrogen was used for directional freezing, and freeze-drying was performed (-72°C, 2 Pa, 48 h) to obtain CF25 aerogel.

[0108] Step S3: The CF25 composite aerogel prepared in step S2 was immersed in a PW melt and vacuum treated, then taken out and naturally cooled to room temperature to obtain a final PW@CF25 composite phase change material.

[0109] Specifically, step S31: 20 g of PW was added into an aluminum tank and moved into a vacuum oven at 80°C to completely melt, then the CF25 aerogel prepared in step S2 was immersed in the PW melt and vacuum treated (80 Pa, 24 h) to make the PW fully enter the CF25 aerogel, and the PW@CF25 composite phase change material was obtained by taking it out and wiping the excess PW melt on the surface with a soft fabric.

[0110] Example 7

[0111] A PW@CG5F25 composite phase change material was prepared by the following method:

[0112] Step S1: flower-like ZnCo-ZIF was prepared by hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy was carried out to obtain flower-like ZnCo-ZIF@PPy (referred to as F) photo-thermal filler;

[0113] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution B;

[0114] Step S12: under the condition of 500 rpm stirring, solution B of step S11 was slowly dropped into solution A, and ultrasonic treatment was carried out at 240 W power for 0.25 h, then the obtained uniform mixed solution was transferred to a 105℃ high-pressure reaction kettle for hydrothermal reaction for 3 h, and centrifugal washing was carried out in sequence using CH3OH, C2H6O and DIW (5000 rpm, 5 min), the precipitate was dispersed in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0115] Step S13: 0.1 mL of C4H5N was dropped into 50 mL of ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and uniform mixing was carried out under the condition of 1500 rpm strong stirring for 0.5 h, then 2.353 g of DBSA was slowly dropped, and transferred to an ice-water bath at 2-10℃ for stirring (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10℃ for 6 h, so that C4H5N was polymerized on the surface of flower-like ZnCo-ZIF, then the reaction product was centrifugally washed in sequence using C2H6O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) photo-thermal filler.

[0116] Step S2: a uniform dispersion of CNF / GNP5 was prepared, and the F photo-thermal filler obtained in step S1 was added to uniformly disperse it, and then freeze-drying was carried out to obtain CNF / GNP5 / F25 (referred to as CG5F25) composite aerogel;

[0117] Specifically, step S21: 0.2 g of GNP powder was gradually added to the uniform water dispersion of CNF (10 mg / mL), and magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were cyclically carried out for 3 times to obtain a uniform CNF / GNP5 uniform dispersion;

[0118] Step S22: 1.0 g of F photo-thermal filler prepared in step S1 was gradually added into the CNF / GNP5 homogeneous dispersion liquid prepared in step S21, and strong stirring was carried out at 2000 rpm for 6 h to obtain a CNF / GNP5 / F25 (abbreviated as CG5F25) homogeneous mixed dispersion liquid;

[0119] Step S23: The CG5F25 homogeneous dispersion liquid obtained in step S22 was poured into an aluminum cap and moved into a low-temperature refrigerator for gelation. Then, directional freezing was carried out using liquid nitrogen, and freeze-drying was carried out (-72℃, 2Pa, 48h) to obtain a CG5F25 aerogel.

[0120] Step S3: The CG5F25 composite aerogel prepared in step S2 was immersed in a PW melt and vacuum treated. Then, it was taken out and naturally cooled to room temperature to obtain a final PW@CG5F25 composite phase change material.

[0121] Specifically, step S31: 20 g of PW was added to an aluminum pot and moved into a 80℃ vacuum oven for complete melting. Then, the CG5F25 aerogel prepared in step S2 was immersed in the PW melt and vacuum treated (80Pa, 24h) to make the PW fully enter the CG5F25 aerogel. It was taken out and the excess PW melt on the surface was wiped off using a soft fabric to obtain a final PW@CG5F25 composite phase change material.

[0122] Example 8

[0123] A PW@CG10F25 composite phase change material was prepared by the following method:

[0124] Step S1: flower-like ZnCo-ZIF was prepared by a hydrothermal method, and then low-temperature chemical deposition (poly-pyrrole) PPy was carried out to obtain flower-like ZnCo-ZIF@PPy (abbreviated as F) photo-thermal filler;

[0125] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution A. At the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution B;

[0126] Step S12: Solution B of step S11 was slowly dripped into solution A under stirring condition of 500 rpm, and ultrasonic treatment was carried out at a power of 240 W for 0.25 h, then the obtained uniform mixed solution was transferred into a high-pressure reaction kettle at 105 ℃, and hydrothermal reaction was carried out for 3 h, and centrifugal washing was carried out in sequence using CH 3 OH, C 2 H 6 O and DIW (5000 rpm, 5 min), the precipitate was dispersed in DIW to obtain a ZnCo-ZIF uniform water dispersion;

[0127] Step S13: 0.1 mL of C 4 H 5 N was dripped into 50 mL of the ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and uniform mixing was carried out under strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly dripped, and stirring was carried out in an ice-water bath at 2-10 ℃ (1000 rpm, 0.5 h), and 50 mL of FeCl 3 ·6H 2 O (0.6 M) was added, and the temperature was kept at 2-10 ℃ for 6 h, so that C 4 H 5 N was polymerized on the surface of the flower-like ZnCo-ZIF, then centrifugal washing was carried out in sequence using C 2 H 6 O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) photo-thermal filler.

[0128] Step S2: A CNF / GNP 10 uniform dispersion was prepared, and the F photo-thermal filler obtained in step S1 was added and uniformly dispersed, and then freeze-drying was carried out to obtain a CNF / GNP 10 / F 25 (referred to as CG 10 F 25) composite aerogel;

[0129] Specifically, step S21: 0.4 g of GNP powder was gradually added into a CNF uniform water dispersion (10 mg / mL), and magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were carried out in cycles for 3 times to obtain a uniform CNF / GNP 10 uniform dispersion;

[0130] Step S22: 1.0 g of the F photo-thermal filler prepared in step S1 was gradually added into the CNF / GNP 10 uniform dispersion prepared in step S21, and strong stirring was carried out at 2000 rpm for 6 h to obtain a CNF / GNP 10 / F 25 (referred to as CG 10 F 25) uniform mixed dispersion;

[0131] Step S23: The CG 10 F 25 uniform dispersion obtained in step S22 was poured into an aluminum cover, and was moved into a low-temperature refrigerator for gelation, then directional freezing was carried out using liquid nitrogen, and freeze-drying was carried out (-72 ℃, 2 Pa, 48 h) to obtain a CG 10 F 25 aerogel.

[0132] Step S3: The CG10F25 composite aerogel prepared in step S2 is immersed in the PW melt and vacuum treated, then taken out and naturally cooled to room temperature to obtain the final PW@CG10F25 composite phase change material.

[0133] Specifically, step S31: 20 g of PW is added to an aluminum tank and moved into a vacuum oven at 80°C to completely melt, then the CG10F25 aerogel prepared in step S2 is immersed in the PW melt and vacuum treated (80 Pa, 24 h) to make the PW fully enter the CG10F25 aerogel, and then taken out and wiped with a soft fabric to remove the excess PW melt on the surface to obtain the final PW@CG10F25 composite phase change material.

[0134] Example 9

[0135] A PW@CG20F25 composite phase change material is prepared by the following method:

[0136] Step S1: flower-like ZnCo-ZIF is prepared by a hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy is performed to obtain flower-like ZnCo-ZIF@PPy (referred to as F) photo-thermal filler;

[0137] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O are added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI is added to 17.5 mL of CH3OH and magnetically stirred at 500 rpm for 0.5 h to obtain a uniform solution B;

[0138] Step S12: under the condition of 500 rpm stirring, solution B of step S11 is slowly dropped into solution A, and ultrasonic treatment is performed at a power of 240 W for 0.25 h, then the obtained uniform mixed solution is transferred to a high-pressure reaction kettle at 105°C, and hydrothermal reaction is performed for 3 h, and centrifugal washing is performed in sequence using CH3OH, C2H6O and DIW (5000 rpm, 5 min), the precipitate is dispersed in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0139] Step S13: 0.1 mL of C4H5N was added into 50 mL of ZnCo-ZIF aqueous dispersion (10 mg / mL) obtained in step S12, and was uniformly mixed by strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly added, transferred into an ice water bath at 2-10°C and stirred (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10°C for 6 h, so that C4H5N was polymerized on the surface of the flower-like ZnCo-ZIF, then the reaction product was washed by centrifugation (5000 rpm, 5 min) using C2H6O and DIW in sequence, and ZnCo-ZIF@PPy (referred to as F) photo-thermal filler was obtained.

[0140] Step S2: CNF / GNP20 / F25 (referred to as CG20F25) composite aerogel was obtained by preparing a CNF / GNP20 uniform dispersion liquid, adding the F photo-thermal filler obtained in step S1 into the CNF / GNP20 uniform dispersion liquid, uniformly dispersing the F photo-thermal filler, and freeze-drying.

[0141] Specifically, step S21: 0.8 g of GNP powder was gradually added into a CNF uniform aqueous dispersion liquid (10 mg / mL), and the magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) were cycled for 3 times to obtain a uniform CNF / GNP20 uniform dispersion liquid.

[0142] Step S22: 1.0 g of F photo-thermal filler prepared in step S1 was gradually added into the CNF / GNP20 uniform dispersion liquid prepared in step S21, and was uniformly mixed by strong stirring at 2000 rpm for 6 h to obtain a CNF / GNP20 / F25 (referred to as CG20F25) uniform mixed dispersion liquid.

[0143] Step S23: The CG20F25 uniform dispersion liquid obtained in step S22 was poured into an aluminum cap and moved into a low-temperature refrigerator for gelation, then was directionally frozen using liquid nitrogen, and was freeze-dried (-72°C, 2 Pa, 48 h) to obtain a CG20F25 aerogel.

[0144] Step S3: The CG20F25 composite aerogel prepared in step S2 was immersed in a PW melt and was vacuum treated, then was taken out and naturally cooled to room temperature to obtain a final PW@CG20F25 composite phase change material.

[0145] Specifically, step S31: 20 g of PW was added into an aluminum tank and moved into a vacuum oven at 80°C to completely melt, then the CG20F25 aerogel prepared in step S2 was immersed in the PW melt, vacuum treatment (80 Pa, 24 h) was carried out to make the PW fully enter the CG20F25 aerogel, and the PW@CG20F25 composite phase change material was obtained by removing the excess PW melt on the surface of the aerogel using a soft fabric.

[0146] Example 10

[0147] A PW@CG25F25 composite phase change material was prepared by the following method:

[0148] Step S1: flower-like ZnCo-ZIF was prepared by a hydrothermal method, then low-temperature chemical deposition (poly-pyrrole) PPy was carried out to obtain flower-like ZnCo-ZIF@PPy (referred to as F) light-heat filler.

[0149] Specifically, step S11: 825 mg of Co(NO3)2·6H2O and 275 mg of Zn(NO3)2·6H2O were added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution A; at the same time, 650 mg of 2-MI was added to 17.5 mL of CH3OH, and magnetic stirring was carried out at 500 rpm for 0.5 h to obtain a uniform solution B;

[0150] Step S12: under the condition of 500 rpm stirring, solution B of step S11 was slowly dropped into solution A, and ultrasonic treatment was carried out at a power of 240 W for 0.25 h, then the obtained uniform mixed solution was transferred to a high-pressure reaction kettle at 105°C, and hydrothermal reaction was carried out for 3 h, and centrifugal washing was carried out in sequence using CH3OH, C2H6O and DIW (5000 rpm, 5 min), the precipitate was dispersed in DIW to obtain a uniform water dispersion of ZnCo-ZIF;

[0151] Step S13: 0.1 mL of C4H5N was dropped into 50 mL of ZnCo-ZIF water dispersion (10 mg / mL) obtained in step S12, and uniform mixing was carried out under the condition of strong stirring at 1500 rpm for 0.5 h, then 2.353 g of DBSA was slowly dropped, and stirring was carried out in a 2-10°C ice water bath (1000 rpm, 0.5 h), and 50 mL of FeCl3·6H2O (0.6 M) was added, and the temperature was kept at 2-10°C for 6 h, so that C4H5N was polymerized on the surface of the flower-like ZnCo-ZIF, then centrifugal washing was carried out in sequence using C2H6O and DIW (5000 rpm, 5 min) to obtain ZnCo-ZIF@PPy (referred to as F) light-heat filler.

[0152] Step S2: preparing a CNF / GNP25 homogeneous dispersion liquid, and adding the F photothermal filler obtained in step S1 into the CNF / GNP25 homogeneous dispersion liquid, uniformly dispersing the F photothermal filler, and then freeze-drying to obtain a CNF / GNP25 / F25 (abbreviated as CG25F25) composite aerogel;

[0153] Specifically, step S21: gradually adding 1.0 g of GNP powder into a CNF homogeneous aqueous dispersion liquid (10 mg / mL), and performing magnetic stirring (1000 rpm, 2 h) and ultrasonic treatment (240 W, 1 h) for 3 times in cycles to obtain a homogeneous CNF / GNP25 homogeneous dispersion liquid;

[0154] Step S22: gradually adding 1.0 g of the F photothermal filler prepared in step S1 into the CNF / GNP25 homogeneous dispersion liquid prepared in step S21, and performing strong stirring at 2000 rpm for 6 h to obtain a CNF / GNP25 / F25 (abbreviated as CG25F25) homogeneous mixed dispersion liquid;

[0155] Step S23: pouring the CG25F25 homogeneous dispersion liquid obtained in step S22 into an aluminum cap, and moving into a low-temperature refrigerator for gelation, then using liquid nitrogen for directional freezing, and performing freeze-drying (-72℃, 2 Pa, 48 h) to obtain a CG25F25 aerogel.

[0156] Step S3: immersing the CG25F25 composite aerogel prepared in step S2 into a PW melt, and performing vacuum treatment, then taking it out and naturally cooling to room temperature to obtain a final PW@CG25F25 composite phase change material.

[0157] Specifically, step S31: adding 20 g of PW into an aluminum pot, and moving into a 80℃ vacuum oven to completely melt, then immersing the CG25F25 aerogel prepared in step S2 into the PW melt, and performing vacuum treatment (80 Pa, 24 h) to make the PW fully enter the CG25F25 aerogel, taking it out, and using a soft fabric to wipe off the excess PW melt on the surface to obtain a final PW@CG25F25 composite phase change material.

[0158] Comparative Example

[0159] A PW@CNF composite phase change material, and the preparation method is as follows:

[0160] A 10 mg / mL CNF homogeneous dispersion was subjected to directional freeze-drying (-72 °C, 2 Pa, 48 h) to obtain a CNF aerogel; then, 20 g of PW was weighed into an aluminum can and was moved into a vacuum oven at 80 °C to melt completely; subsequently, the CNF aerogel was immersed into the PW melt and was subjected to vacuum treatment (80 Pa, 24 h) to make the PW enter the CNF aerogel sufficiently, and was taken out and the surface excess PW melt was wiped off using a soft fabric to obtain the final PW@CNF composite phase change material. In this comparative example, the GNP and F fillers used in the examples were not added, and the heat conduction and light-heat conversion capacity of the obtained PW@CNF composite phase change material was obviously not as good as that of the examples of the application.

[0161] During the research of the application, a large number of experimental researches were carried out, and part of the experimental results are shown in the following tables. Figures 1-8 .

[0162] From Figure 1 It can be seen that the ZnCo-ZIF has a clear flower-like structure, and the pore wall is smooth Figure 1 a). After the surface is deposited with polypyrrole (PPy), the obtained ZnCo-ZIF@PPy (F) also shows a similar flower-like structure, but the pore wall is relatively rough Figure 1 b). From the FTIR spectrum Figure 1 c) and the XRD pattern Figure 1 d), it can be found that the F has all the characteristic peaks of the ZnCo-ZIF, and no new peak appears. These phenomena show that the PPy is deposited on the surface of the ZnCo-ZIF as a thin film, and is combined with each other through physical means (such as hydrogen bond, surface tension and van der Waals force, etc.).

[0163] From Figure 2 It can be seen that the CG15F25 composite aerogel presents a neatly arranged bundle of tubes on the longitudinal section Figure 2 a1), and presents a honeycomb-like porous network on the transverse section Figure 2 b1), indicating a significant anisotropic pore structure. Further magnification of the SEM image shows that the F light-heat fillers are mainly located on the surface of the skeleton or the pore wall Figure 2 a2 and b2), which will benefit the auxiliary adsorption of PCMs. In addition, the GNP is "bridged" with each other, and a heat conduction network for phonon conduction is constructed.

[0164] From Figure 3 It can be seen that the cross sections of the PW@CNF, PW@CG15, PW@CF25, PW@CG5F25, PW@CG15F25 and PW@CG25F25 have almost no obvious cracks and pores Figure 3 a1-f1). Further magnification of the SEM shows that the PW is tightly wrapped in the CGxFy skeleton Figure 3a2-f2), which is due to the good hydrophobicity of PW and CGxFy backbones and the strong interfacial interaction between the PW matrix and the CGxFy pore wall.

[0165] Depend on Figure 4 It can be seen that the PW placed on the 80℃ hot plate gradually melted and turned into a flowing melt within 250s ( Figure 4 a), indicating that during the endothermic phase transition, PW molecules are prone to move freely and leak. However, only a small amount of leakage occurred in PW@CG15, indicating that the three-dimensional interconnected porous skeleton can play a role in restricting and adsorbing molten PW. After the introduction of F, the leakage of PW@CG15F15 was greatly reduced. This is because the small pore size and high specific surface area of ​​F increased the surface tension and capillary force to further enhance the adsorption of PW. With the increase of GNP content, the leakage of the obtained PW@CG25F15 continued to decrease, and after loading 500g weight, the leakage was almost negligible and maintained its original shape. The above results show that the good adsorption of PW by the CGxFy double network (aerogel skeleton and flower-like F) gives PW@CGxFy outstanding shape stability and mechanical strength. It is worth noting that the FTIR spectra of PW@CNF, PW@CG15, PW@CF15 and PW@CG15F15 are basically consistent with those of PW and CGxFy ( Figure 4 b), indicating that the absorption between PW and CGxFy aerogel mainly relies on physical interaction rather than chemical interaction. In addition, the peak positions of PW@CNF, PW@CG15, PW@CF15 and PW@CG15F15 are highly similar to those of PW, with almost no position deviation and no new diffraction peaks appearing ( Figure 4 c) This result indicates that the porous CGxFy framework has almost no effect on the crystalline structure of PW during the impregnation process, which will help PW maintain its original phase change properties.

[0166] Depend on Figure 5 It can be seen that PW has a higher melting enthalpy (ΔH m ,193.7J / g) and crystallization enthalpy (ΔH c ,201.6J / g)( Figure 5 a) The phase transition enthalpy of PW@CNF and PW@CGxF25 is only slightly lower than that of PW, which is mainly due to the fact that the CNF and CGxF25 frameworks have no phase transition properties. PW@CG25F25 with both GNP and F filling contents of 5.89wt% still shows a higher ΔH m (178.8 J / g) and ΔHc (181.2 J / g), the melting and crystallization enthalpy efficiencies are as high as 92.31% and 89.88%, respectively. In addition, the melting temperature (T m ) and crystallization temperature (T c57.69 °C and 52.13 °C, respectively Figure 5 b), T m (~57 °C) and T c (~52 °C) are very close to PW. It can be seen that the PW@CGxF25 composite phase change material has ideal heat storage potential. The representative PW@CG25F25 composite phase change material has basically unchanged phase change parameters (AH m , AH c , T m and T c ) during 100 heating-cooling cycles Figure 5 c and Figure 5 d), indicating that it has excellent cycle stability in heat storage / release and can meet long-term practical application.

[0167] It can be seen from Figure 6 that the thermal conductivity (TC) of PW is only 0.22 Wm -1 K -1 , which is not conducive to the rapid conduction of heat energy. The TC of PW@CNF, PW@CF15 and PW@CF25 is only 0.22, 0.24 and 0.24 0.22 Wm -1 K -1 ( Figure 6 a), indicating that the CNF and F network has little ability to improve heat conduction. The TC of PW@CG15 can reach 0.65 Wm -1 K -1 , which indicates that GNP can construct an effective heat conduction network. When the F filler concentration gradually increases from 5 mg / mL to 25 mg / mL, the corresponding TC of PW@CG15Fy (0.62-0.66 Wm-1K-1) is close to that of PW@CG15 (0.65 Wm -1 K -1 )( Figure 6 a), indicating that the F filler has little effect on the GNP heat conduction path in this concentration range. However, the TC of PW@CG15F35 suddenly decreases to 0.52 Wm -1 K -1 because the excessive F filler hinders the effective lapping of the GNP heat conduction network. It can be seen from Figure 6 b that the TC of PW@CGxF25 gradually increases with the increase of GNP content. When the GNP content is 25 mg / mL, the TC reaches 0.79 Wm -1 K -1 ( Figure 6 ), and the TC enhancement rate is as high as 259.09%. It can be seen that the prepared PW@CGxF25 composite phase change material has excellent heat storage / release capacity.

[0168] It can be seen fromFigure 7 It can be seen that ZnCo-ZIF has a strong absorbance (0.92-1.08) in the UV (200-400nm) wavelength range, while the absorbance in the visible (400-760nm) and near-infrared (760-2500nm) wavelength ranges decreases sharply with the increase of wavelength ( Figure 7 a), which is not conducive to the effective absorption of sunlight. The flower-shaped F filler obtained after depositing PPy has an absorbance of 0.95-1.65 in the full UV-visible-near infrared spectrum (200-2500nm), which is comparable to the absorbance of pure PPy (1.08-1.81), indicating that F has outstanding light absorption properties. The absorbance of GNP is between 0.44 and 0.75, indicating that GNP has strong photon capture ability. The absorbance of PW@CNF in the full UV-vis-NIR wavelength range is weak and fluctuating, with an average value of only 0.36 ( Figure 7 b), which is not conducive to sunlight capture. After the introduction of GNPs, the average absorbance of PW@CG25 across the entire wavelength range was 1.05, showing stable and ideal absorbance. Further compounding with flower-like F resulted in PW@CG25F25 with an average absorbance of 1.30, demonstrating that flower-like F and GNPs synergistically enhance the light-harvesting ability of the PW@CGxFy composite phase-change material.

[0169] At 100mW / cm 2 Under the simulated sunlight, the photothermal response of PW@CNF is relatively weak, with the top and bottom temperatures being only 54.9℃ and 56.8℃, respectively. Figure 7 c1-c2), the phase transition temperature of PW (58-60℃) is not reached, so no obvious temperature "platform" appears. After adding GN and F, the light-heat conversion performance of PW@CF25, PW@CG15 and PW@CG15F25 is significantly improved, and a typical temperature "platform" appears ( Figure 7 c1-c2). This phenomenon is largely due to the outstanding light absorption and heat conduction capabilities of the CG15F25 framework. After stopping the illumination, the PW@CF25, PW@CG15 and PW@CG15F25 samples showed a clear temperature "platform" around 56.16 ~ 42.28 ° C, which was due to the release of latent heat of the liquid-solid phase change of PW. The above results show that PW@CF25, PW@CG15 and PW@CG15F25 have good light-heat conversion and internal heat transfer properties. Figure 7 As shown in Figure 2, with the increase of GNP content, the temperature of PW@CGxF25 increases faster and the phase transition "platform" time is shorter ( Figure 7d1-d2), which is mainly attributed to the increased GNPs providing more sunlight capture area and creating more efficient thermal conduction pathways. Calculation results show that the light-to-heat conversion efficiency (ε) of PW@CG5F25, PW@CG10F25, PW@CG15F25, PW@CG20F25, and PW@CG25F25 reached 64.0%, 66.2%, 77.5%, 82.1%, and 93.4%, respectively, demonstrating that the prepared PW@CGxF25 composite phase change material has outstanding light-to-heat conversion capabilities.

[0170] Depend on Figure 8 It can be seen that at 100mW / cm 2 Under simulated solar radiation, the PW@CNF co-assembled photo-thermal-electric (STE) device exhibited a weak open circuit voltage (V OC , 85.6mV) and short-circuit current (I SC , 14.7mA)( Figure 8 a1-a2), which is attributed to the extremely weak light-to-heat conversion ability of PW and CNF. OC -Time and I SC - The time curve shows V OC and I SC This is because the PW@CG5F25 with a lower TC requires a longer solid-liquid phase transition time and cannot transfer the captured photothermal energy to TEG in time. With the increase of GNP content, the V OC and I SC Specifically, the STE system based on PW@CG25F25 outputs a stable V OC and I SC Up to 203.0mV and 33.8mA respectively ( Figure 8 a1-a2). This phenomenon is mainly attributed to two factors: on the one hand, the increase of GNPs enhances the light-heat conversion ability, making the sample generate higher temperature; on the other hand, the more GNPs there are, the more perfect the heat conduction network is, thus increasing the temperature of the TEG hot end. The STE device built with PW@CG25F25 outputs V OC and I SC Increases uniformly with increasing light intensity ( Figure 8 b1-b2). When reaching steady state, the power consumption is 80, 100 and 120 100mW / cm 2 Under the radiation of STE system, V OC Up to 196.5, 203, and 214mV, I SC29.9, 33.8 and 36.6 mA, respectively. This is because: the stronger the sunlight, the higher the photon energy of PW@CG25F25 for light-heat conversion, resulting in a larger temperature difference across the TEG. It can be seen that the STE generator based on PW@CG25F25 can effectively convert different intensities of sunlight into electrical energy. In addition, from the time curves of V Figure 8 c1-c2 can be seen that the V OC - time and I SC - time curves of the STE system built by PW@CG25F25 basically do not change under 5 cycles of on-off light illumination. When reaching steady state, the output V OC of the 1st, 2nd, 3rd, 4th and 5th cycles are 200, 201, 205, 206 and 207 mV, respectively, and the output I SC are 34.0, 34.3, 34.1, 34.2 and 33.3 mA, respectively. This result shows that the STE system built by PW@CG25F25 has outstanding cyclic stability, which provides a guarantee for its long-term practical application in capturing solar energy. In summary, the STE system built by PW@CGxF25 and TEG not only can output ideal V 2 (203.0 mV) and V OC (33.8 mA) under standard solar irradiation (100 mW / cm OC ), but also has good responsiveness to different intensities of sunlight and stable cyclic performance. It can be seen that the PW@CGxF25 composite phase change material has potential application value in solar-thermal energy conversion to alleviate environmental pollution and energy crisis caused by large consumption of fossil fuels.

[0171] Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacements to part of the technical features, and any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing anisotropic dual-network encapsulated photothermal composite phase change material, characterized in that: The steps include: S1. Flower-shaped ZnCo-ZIF was prepared by hydrothermal method, followed by chemical deposition of PPy to obtain flower-shaped ZnCo-ZIF@PPy, i.e., F photothermal filler; S2, prepare a uniform CNF / GNPx dispersion, and add the F photothermal filler obtained in step S1 into it, After being uniformly dispersed, CNF / GNPx / Fy, namely CGxFy composite aerogel, was obtained by freeze-drying; S3. Immerse the CGxFy composite aerogel prepared in step S2 in a PW melt and perform vacuum treatment. Then, take it out and naturally cool it to room temperature to obtain the final PW@CGxFy composite phase change material; wherein x represents the concentration of GNPs, ranging from 5 to 25 mg / mL; y represents the filling concentration of F, ranging from 5 to 35 mg / mL.

2. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 1, characterized in that: In step S1, the specific preparation includes the following: S11. Co(NO3)2·6H2O and Zn(NO3)2·6H2O were added to CH3OH and magnetically stirred to obtain a uniform solution A. Simultaneously, 2-MI was added to CH3OH and magnetically stirred to obtain a uniform solution B. S12. Under stirring, solution B was slowly added dropwise to solution A and ultrasonic treatment was performed; then, the obtained uniform mixed solution was transferred to an autoclave for hydrothermal reaction, and centrifuged and washed with CH3OH, C2H6O, and DIW in sequence, and the precipitate was dispersed in DIW to obtain a uniform aqueous dispersion of ZnCo-ZIF; S13. C4H5N is dropped into the uniform aqueous dispersion of ZnCo-ZIF obtained in step S12, and vigorously stirred to mix it evenly. Subsequently, DBSA is slowly dropped, and the mixture is transferred to an ice-water bath for stirring. FeCl3·6H2O is added thereto, and the mixture is kept at a low temperature to allow C4H5N to polymerize on the surface of the flower-like ZnCo-ZIF. The reaction product is then centrifuged and washed with C2H6O and DIW in sequence to obtain ZnCo-ZIF@PPy, i.e., F photothermal filler.

3. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 2, characterized in that: In step S11, the mass volume ratio of Co(NO3)2·6H2O, Zn(NO3)2·6H2O, 2-MI and CH3OH is 825 mg:275 mg:650 mg:17.5 mL; the magnetic stirring speed and time are 200-700 rpm and 0.3-1 h, respectively; In step S12, the stirring speed is 200-700 rpm, the power and time of ultrasonic treatment are 240 W and 0.1-0.5 h respectively, the temperature and time of the hydrothermal reaction are 90-120 °C and 2-5 h respectively, and the speed and time of centrifugation are 3000-6000 rpm and 2-8 min respectively.

4. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 2, characterized in that: In step S13, the mass volume ratio of DBSA, C4H5N, ZnCo-ZIF and FeCl3·6H2O is 2.353 g:0.1 mL:40 mL:50 mL; the concentration of the ZnCo-ZIF aqueous dispersion is 6-10 mg / mL; the speed and time of vigorous stirring are 1000-2000 rpm and 0.5-2 h, respectively; the temperature of the ice-water bath is 2-10°C, and the stirring speed and time in the ice-water bath are 500-1500 rpm and 0.5-2 h, respectively; the concentration of the FeCl3·6H2O is 0.3-0.8 M, the temperature and time of low temperature maintenance are 0-4°C and 2-6 h, respectively, and the speed and time of centrifugation are 3000-7000 rpm and 2-8 min, respectively.

5. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 1, characterized in that: In step S2, the specific preparation includes the following: S21, gradually adding GNP powder to the CNF uniform aqueous dispersion, cyclically performing magnetic stirring and ultrasonic treatment to obtain a uniform CNF / GNPx uniform dispersion; S22, gradually adding the prepared F photothermal filler to the CNF / GNPx uniform dispersion prepared in step S21, and vigorously stirring to obtain a CNF / GNPx / Fy, i.e., CGxFy uniform dispersion; S23. Pour the CGxFy uniform dispersion obtained in step S22 into an aluminum cover and move it into a low-temperature refrigerator for gelation. Then, use liquid nitrogen for directionally freezing and freeze-drying to obtain CGxFy aerogel.

6. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 5, characterized in that: In step S21, the concentration of the CNF uniform aqueous dispersion is 3-12 mg / mL, the concentration of the GNP is 5-25 mg / mL, the speed and time of the magnetic stirring are 500-2000 rpm and 1-3 h, respectively, the ultrasonic power and time are 240 W and 1-4 h, respectively, and the number of cycles is 2-5 times.

7. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 5, characterized in that: In step S22, the concentration of the F photothermal filler is 5-35 mg / mL, and the strong stirring speed and time are 1000-3000 rpm and 4-8 h, respectively; In step S23, the temperature of the low-temperature refrigerator is 0-4°C, and the gelation time is 8-16 hours; the temperature, pressure and time of freeze drying are -72°C, 2 Pa and 24-72 hours respectively.

8. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 1, characterized in that: In step S3, the specific preparation includes the following: PW is added to an aluminum can and moved into a vacuum oven to completely melt it. Then, the CGxFy composite aerogel prepared in step S2 is immersed in the PW melt and vacuum treated to allow the PW to fully enter the CGxFy aerogel. It is taken out and the excess PW melt on the surface is wiped off with a soft fabric to obtain the final PW@CGxFy composite phase change material.

9. The method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to claim 8, characterized in that: The mass ratio of the PW to the CGxFy composite aerogel is 20:1-5; the temperature of the vacuum oven is 60-90° C., and the pressure and time of the vacuum treatment are 80 Pa and 18-32 h.

10. An application of a photothermal composite phase change material prepared by the method for preparing anisotropic dual-network encapsulated photothermal composite phase change material according to any one of claims 1 to 9, characterized in that: The photothermal composite phase change material is used as a photothermal conversion material in a photothermal-electric generator.

Citation Information

Patent Citations

  • Flexible hydrophobic anisotropic cellulose nanofiber aerogel phase-change composite material and preparation method thereof

    CN114032071A

  • Composite phase change material with hydrophobic and efficient photothermal conversion performance and preparation method and application thereof

    CN117025175A